The Use of Leafleat Media on Student Learning Creativity in Pkn Learning in Class V SDN 70 Banda Aceh - Sari, Yuliana; Sulaiman, Sulaiman; vitoria, linda (Elementary Education Research, 2023)
The purpose of this study was to describe the learning creativity of students in Civics learning in Class V SDN 70 Banda Aceh by using leaflet media. The approach in research is qualitative and descriptive research type. The subjects studied were 32 students of class V SD Negeri 70 Banda Aceh with data collection techniques namely observation and interviews. This research has results that can be stated that of the 7 indicators of learning creativity, almost all students in the class have implemented these indicators in learning, starting from the activities of students often asking questions during the learning process, students try to find references from other sources, for example from theme books, during learning they always ask questions according to the material being discussed at the time, they are active in giving opinions during discussions with the teacher or with their group mates, they are confident and willing to express opinions without being rewarded, they are confident in their opinions each, they are also enthusiastic and able to interact and do tasks well with their group mates. However, there is one indicator that they have not implemented properly, namely being able to submit thoughts and ideas that are different from other people, which is indicated when they are presenting the results of their group work, they have not been able to account for the ideas they put forward during the presentation.